2007
DOI: 10.1590/s0482-50042007000100013
|View full text |Cite
|
Sign up to set email alerts
|

Calcinose na infância, um desafio terapêutico

Abstract: A calcinose é uma complicação comum e incapacitante da dermatomiosite. Ela constitui uma característica marcante da doença, ocorrendo principalmente em pacientes pediátricos. Pouco se sabe a respeito de sua fisiopatologia e não existe um tratamento reconhecido universalmente. Este trabalho relata dois casos de dermatomiosite juvenil e calcinose grave com melhora clínica com o uso do alendronato e do diltiazen em um paciente e da imunoglobulina endovenosa em outro.Palavras-chave: dermatomiosite juvenil, calcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(43 reference statements)
0
3
0
2
Order By: Relevance
“…The treatment of calcinosis is itself controversial, since spontaneous involution of the condition can even occur. 10,29 Reports exist of good efficacy and absent or rare adverse events being obtained with EDTA, diltiazem and bisphosphonates (alendronate or pamidronate), and also with surgical excision and localized infiltration of triamcinolone hexacetonide, 18,[26][27][28][29][30][31][32][33] as was used with some of the patients studied here.…”
Section: Resultsmentioning
confidence: 99%
“…The treatment of calcinosis is itself controversial, since spontaneous involution of the condition can even occur. 10,29 Reports exist of good efficacy and absent or rare adverse events being obtained with EDTA, diltiazem and bisphosphonates (alendronate or pamidronate), and also with surgical excision and localized infiltration of triamcinolone hexacetonide, 18,[26][27][28][29][30][31][32][33] as was used with some of the patients studied here.…”
Section: Resultsmentioning
confidence: 99%
“…Calcinosis is known to result from persistent disease activity, poor treatment adherence, and therapy refractoriness. 3,9,22,28 It is worth emphasizing that calcinosis manifested in 10 patients during disease course even after six months of beginning therapy and in patients with good adherence to treatment, and no association was observed between non-adherence and the appearance of that complication. The association of age and higher frequency of calcinosis has neither been reported in other studies, nor found in ours.…”
Section: Discussionmentioning
confidence: 99%
“…A patogênese é desconhecida, mas parece envolver a ação de células inflamatórias, citocinas e proteínas da matriz mineralizada, como osteocalcina. Atraso no início do tratamento, vasculopatia e doença grave são fatores de risco para o aparecimento de calcinose nesses pacientes 15 .…”
Section: Discussionunclassified
“…Em nosso estudo, a paciente apresentou calcificações, dado concordante com outros trabalhos nos quais a frequencia de calcificações é alta 17,18. A paciente descrita apresentou limitações importantes em AVD'S devido encurtamentos, fraquezas musculares e quadro álgico à movimentação articular, caracteristicas próprias desta afecção 15,19 .…”
Section: Discussionunclassified